Дослідження та аналіз механізмів виявлення та запобігання атакам типу ddos на сервери - Топіха, Т. Б. (ХНУРЕ, 2024)
The first DDoS attacks appeared in 1996. However, this phenomenon attracted special attention in 1999, when the world's giants - Amazon, Yahoo, CNN, eBay, and E-Trade - were put out of working condition. And to take urgent measures to solve the problem began only in 2000, when again were committed impact on the servers of important companies. Also at this moment russia is using DDoS attacks to undermine the performance of important structures in Ukraine. And even though the attack has existed for more than 20 years, due to the modernization of the attack algorithm it is possible to inflict quite severe damage to the target of the attack
Keywords: запобігання атакам на сервери; атака типу ddos